Gay Synagogue News - Gay & Lesbian Synagogue News. (New York : Congregation Beth Simchat Torah, 1985)
Fonds Suzan Daniel (FSD)
Periodiciteit : ?
Redactie : Box 1270, New York, NY 10116
Vanaf (1987) jan : Gay & Lesbian Synagogue News
Engels
Periodiek